2006
DOI: 10.1124/jpet.105.095018
|View full text |Cite
|
Sign up to set email alerts
|

3-[2-[4-(3-Chloro-2-methylphenylmethyl)-1-piperazinyl]ethyl]-5,6-dimethoxy-1-(4-imidazolylmethyl)-1 H-indazole Dihydro-chloride 3.5 Hydrate (DY-9760e) Is Neuroprotective in Rat Microsphere Embolism: Role of the Cross-Talk between Calpain and Caspase-3 through Calpastatin

Abstract: Microsphere embolism (ME)-induced cerebral ischemia can elicit various pathological events leading to neuronal death. Western blotting and immunohistochemical studies revealed that expression of calpastatin, an endogenous calpain inhibitor, decreased after ME induction. Calpain activation after ME was apparently due to, in part, a decrease in calpastatin in a late phase of neuronal injury. The time course of that decrease also paralleled caspase-3 activation. In vitro studies demonstrated that calpastatin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Another interesting approach to modulating AIF-mediated PCD via calpain regulation relies on the control of calpastatin, an endogenous inhibitor of calpains. DY-9760e can rescue neurons and cardiomyocytes from ischemic injury by inhibiting proteolysis of calpastatin (96), and can also provide neuroprotection in cerebral ischemia through the inhibition of the calpain-induced fodrin breakdown (97). More recent works have demonstrated the beneficial effects of calpain inhibitors such as MDL-28170 in a rat model of Parkinson's disease (98) or PD150606 in photoreceptors of a retinitis pigmentosa rat model (99).…”
Section: Therapeutic Strategies Targeting Aif-mediated Caspase-indepementioning
confidence: 99%
“…Another interesting approach to modulating AIF-mediated PCD via calpain regulation relies on the control of calpastatin, an endogenous inhibitor of calpains. DY-9760e can rescue neurons and cardiomyocytes from ischemic injury by inhibiting proteolysis of calpastatin (96), and can also provide neuroprotection in cerebral ischemia through the inhibition of the calpain-induced fodrin breakdown (97). More recent works have demonstrated the beneficial effects of calpain inhibitors such as MDL-28170 in a rat model of Parkinson's disease (98) or PD150606 in photoreceptors of a retinitis pigmentosa rat model (99).…”
Section: Therapeutic Strategies Targeting Aif-mediated Caspase-indepementioning
confidence: 99%
“…The neuronal death in penumbra is predominant in apoptosis, while that in core is predominant in necrosis (Lipton 1999). During focal cerebral ischemia, calpains and caspase-3 are activated and involved in the ischemic neuronal death, which have been demonstrated through investigating the protection of calpain and caspase-3 inhibitors and the proteolysis of substrates, such as microtubule-associated protein-2 (MAP-2), spectrin, and calpastatin (Dawson and Hallenbeck 1996;Endres et al 1998;Lipton 1999;Kambe et al 2005;Han et al 2006).…”
mentioning
confidence: 99%
“…Furthermore, up-regulation of eNOS and iNOS mRNA and protein levels accompanied by generation of nitrotyrosine during BBB disruption suggests that NO functions in that process (27). Consistently, we recently reported that NO and peroxynitrite formation is involved in pathological processes of cerebral ischemia, which may lead to cerebral edema by disrupting microvascular integrity (10,28,29). Of note, inhibition of NOS attenuates BBB disruption in cerebral ischemia or β-amyloid injected animals (10,30).…”
Section: No/ Peroxynitrite Signaling Contributes To Neurovascular Dismentioning
confidence: 54%
“….5 hydrate (DY-9760e), a novel calmodulin antagonist, is a potent inhibitor of calmodulin-dependent NOSs, including eNOS and nNOS (29,43). DY-9760e significantly blocked increases in brain water content and extravasation of Evans Blue dye after ischemia (10,44).…”
Section: Therapeutic Perspectivementioning
confidence: 99%